2008
DOI: 10.1002/poc.1500
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects in the Baeyer–Villiger reaction of acetophenones: a theoretical study

Abstract: This paper reports the first complete theoretical study of substituent effects on the mechanism of the Baeyer-Villiger (BV) reaction in non-polar solvents taking into account the lowest-energy mechanism that has been proposed for this rearrangement which is non-ionic and fully concerted. The BV reaction of p-substituted acetophenones, p-XC 6 H 4 COCH 3 (X ¼ NO 2 , CN, H, CH 3 , OCH 3 ), with performic (PFA) and trifluoroperacetic (TFPAA) acids, catalyzed by formic (FA) and trifluoroacetic (TFAA) acids, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 37 publications
2
39
1
Order By: Relevance
“…Reyes et al studied the p-substituent effect on the oxidation of acetophenones by means of DFT. 30 They found that X substitution has a similar influence on the migration barrier as in the PTO system. However, for the 1,2-addition step, the substituent effect is insignificant.…”
Section: Resultsmentioning
confidence: 98%
“…Reyes et al studied the p-substituent effect on the oxidation of acetophenones by means of DFT. 30 They found that X substitution has a similar influence on the migration barrier as in the PTO system. However, for the 1,2-addition step, the substituent effect is insignificant.…”
Section: Resultsmentioning
confidence: 98%
“…Various types of aryl, aliphatic, and naphthenic ketones can be successfully electro-oxidated to the corresponding esters and lactones with molecular oxygen (Table 3, entries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], whereas the aryl ketones were less reactive, higher reaction constant current and longer reaction time were needed to reach good to excellent yields (Table 3, entries [1][2][3][4][5][6][7][8][9][10][11][12]. Various functionalities such as alkyl, alkoxy, bromo, trifluoromethyl, acetyl and nitro groups can tolerate the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, many publications in the open literature have been found in synthesis of these types of compounds, and a well known method for such a synthesis constitutes the Baeyer-Villiger oxidation of ketones [3,4]. Traditional methods for performing such a transformation generally involve the use of stoichiometric amount of the strongest oxidizing reagents (e.g., trifluoroperacetic acid, peroxyacetic acid, and perbenzoic acid) [5][6][7][8], and suffer from considerable drawbacks such as low yield, harsh or delicate reaction condition, and a large amount of waste by-products. Various reagents employed as the oxygen donors have been developed for this conversion include sodium perborate [9], potassium peroxydisulfate (K 2 S 2 O 8 ) [10,11], sodium perborate (NaBO 3 ) [11], m-CPBA [12,13], NADPH [14,15], phenylacetone monooxygenase (PAMO) [16], H 2 O 2 [17][18][19][20][21][22], oxone [23], h-SiO 2 ·KHSO 5 [24], and other complexes [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the activating effect, the lower electrophilicity of the carbonyl group ought to lower the reaction rate, but the activation results in an increased basicity of the carbonyl oxygen, which once protonated increases the electrophilicity of the carbonyl carbon promoting the peracid addition. This second effect slightly prevails and speeds up the overall mechanism . A question which then arises is the following: what happens when there are more substituents on the aromatic ring and how varies the selectivity relative to the various groups position?…”
Section: Resultsmentioning
confidence: 99%